Simulation and optimisation of a solar-powered adsorption refrigeration module (2010)
Adsorption refrigeration technology has been intensively investigated in many countries of the world because of its potential for competing with conventional vapour compression refrigeration and its environmental friendliness. A solar-powered adsorption refrigerator using activated carbon/methanol pair was designed and fabricated. A mathematical model was developed based on the thermodynamics of the adsorption process, heat and mass transfer equations of the collector/generator/absorber components and simplified idealization of the condenser and evaporator components. The partial differential equations generated from the analysis were transformed into explicit finite difference forms for numerical solution. The model was used to compute the collector plate, bond and adsorbent temperatures, and the COP. The model was validated by using data from experiments performed on a solar powered activated carbon/methanol refrigerator and from published works. The predicted peak plate, tube and adsorbent temperatures were 102, 88 and 86°C respectively which compared favourably with 109 peak plate, 95 tube, and 85°C adsorbent temperatures from published works. The COP of the modelled refrigerator using imported activated carbon ranged from 0.0340 to 0.0345 compared to 0.0300 to 0.0550 recorded in the literature while the COP achieved from the experimental rig using locally manufactured activated carbon ranged from 0.0163 to 0.0200. Reducing the tube thickness from 5mm to 1.5mm led to a gain of 80.0% in COP. The adsorbent parking density of 550 kg/m3 gave an optimum COP, while a decrease of plate thickness from 1.5mm to 1.0mm increased the COP from 0.0338 to 0.0352.